Tinjauan Surat Edaran Satgas Covid-19 Nomor 20 Tahun 2021 Atas Kebijakan Wajib Karantina Setelah Melakukan Perjalanan Internasional Pada Masa Pandemi Covid-19 Dalam Perspektif Hak Asasi Manusia - Budi Harto; Mahzaniar (Inovasi Pratama Internasional. Ltd, 2022)
The phenomenon of the spread of the corona virus (Covid-19) which is very fast and uncontrolled has made the World Health Organization (WHO) stipulate that Covid-19 as a pandemic on March 12, 2020. In Indonesia, as one of the countries affected by Covid-19, has tried to make several policies in order to suppress the spread and limit the space for the transmission of Covid-19. One of these policies is the regulation of mandatory quarantine for Indonesian Citizens (WNI) and Foreign Citizens (WNA) who have traveled internationally as stated in the Covid-19 Task Force Circular No. 20 of 2021 concerning International Travel Health Protocols During the Covid-19 Pandemic. -19. The policy regarding the obligation to undergo quarantine during the pandemic has the potential for violations in terms of fulfilling human rights. This study examines more specifically the self-quarantine regulations that are placed in hotels with the components of all costs incurred not being borne by the government but by themselves. This type of research uses a normative juridical method with an approach to legislation and concepts related to self-quarantine. This study summarizes that the state policy regarding mandatory quarantine in an emergency situation such as the Covid-19 pandemic is something that is legally allowed, as long as the limitation of human rights is still in the derogable right group (which can be limited in its fulfillment). However, taking such action must be done carefully, and full of wisdom. There are sanctions for violations (such as the case of decision Number 21/Pid.S/2021/PN Tng) regarding escaping from the quarantine center, even though the trial process and case title are brief criminal proceedings, hoping that it will not only cause a deterrent effect on the community , but as an effort to make the public aware of the law and efforts to prevent similar cases from happening and reoccurring.